Sen meets Schumpeter: Introducing structural and dynamic elements into the human capability approach - Dominik Hartmann (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2012)
This paper argues for the necessity and potential of introducing Schumpeter's understanding of economic development as structural change into Amartya Sen's people-oriented development as freedom approach. Sen and other authors on social choice, human development and inequality have effectively promoted - through the United Nations Development Programme - that the expansion of human agency, well-being and capabilities are the means and ends of development (Sen, 1999). However, this approach has lead to a neglect of structural and technological aspects of economic systems such as social network dynamics, technological progress and the structural changes in the variety and balance of economic activities. Innovation driven socioeconomic change has decisive influences on the capabilities of the actors to be active agents in the development processes. For instance, the variety of economic sectors in a country and the access to information and finance networks determine occupational choices and learning opportunities. Economic diversification and social network dynamics follow evolutionary paths that can contribute to human development, but also intrinsically drive success-breeds-success mechanisms and inequality reproduction. Therefore, an agent oriented evolutionary theory of inequality and qualitative change has to take these structural features of economic development into account.
urn:nbn:de:bsz:100-opus-7241
Keywords: 330; Capability Approach; Entwicklung; Evolutionsökonomik; Innovationswettbewerb; Schumpeterismus